Uma análise do comportamento e dos efeitos da carga tributária na economia brasileira no período de 1980 a 2012 - Diniz Filho, José Washington de Freitas (2014)
Since the tax burden has been mensured at the first time in Brazil, in 1947, it has been showing an upward trend behavior, excepted in 1963/64 and 1985, when it has presented a decline in its tendence. In this sense, this study has as it objective discuss the tax burden behavior and verify its effects on aggegated macroeconomic variables. To do so, a recent period with an expressive growth between 1980 and 2012 has been considered. In order to achieve the objective, an Autoregressive Vector (VAC) has been used in order to verify the main macroeconomic aggregated factors behavior after changes uccured in the tax burden. Complementary, a precedence relation between economic variables by Granger causality has been analysed. The application of econometric method, has emphazised that with the exception of the exchange rate, whicch has shown a decreasing behavior after the shock in taxation, the other economic aggregates have shown negative changes in their tendency, also in the period after the tax burden, which have stabilized, in general, after four periods, suggesting that changes in taxation provoke long term effects. So, it can be concluded that expansive effects in tax burden tend to limitate economic growth by longlasting effects caused in economic activity, and also the behavior in real aggregate, however, this effects do not occur in an isolate way, leading an elevated level of dependence and interlinking, including nominal variables, which are many times used as an instrument to achieve economic and political objectives.